Secondhand smoking increased the possibility of hypertension with a significant time and frequency dose-response relationship - Suixia Cao; Jingchun Liu; Yating Huo; Huimeng Liu; Yutong Wang; Binyan Zhang; Kun Xu; Peiying Yang; Lingxia Zeng; Shaonong Dang; Hong Yan; Baibing Mi (Scientific Reports)
Abstract In this research, we investigated whether secondhand smoking (SHS) increases the possibility of hypertension. We used data from the Shaanxi baseline survey of the Regional Ethnic Cohort Study in Northwest China (RECS). Active smoking and SHS were determined by questionnaires. Hypertension was defined as self-reported or objectively measured. Multivariable logistic regression model was performed to estimate the risk of hypertension under active smoking and SHS. Compared to never-smokers, exposure to SHS had a 9% (P = 0.005) higher possibility of hypertension. The adjusted OR for exposure time of ≤ 3 h/week, 3–12 h/week, and > 12 h/week were 1.03 (P = 0.545), 1.10 ( P = 0.040), and 1.15 (P = 0.015), respectively. The adjusted OR for frequency of SHS of 1–2 times/week, 3–5 times/week, and nearly every day were 0.94 (P = 0.421), 1.01 (P = 0.846), and 1.14 (P < 0.001), respectively. Compared to smokers, additional exposure to SHS had a more than threefold increased possibility of having hypertension. The adjusted OR for hypertension was 1.07 (P = 0.254), and 1.23 (P = 0.007) in only smokers and smokers with SHS, respectively. Our study provided evidence that SHS could be a risk factor for hypertension, and additional exposure of active smokers to SHS significantly increases the possibility of hypertension. Reducing the frequency or time of SHS may be effective in preventing hypertension.